"Thank heavens for the lease": histories of shared ownership. Issue 6 (18th August 2018) - Cowan, Dave; Carr, Helen; Wallace, Alison
Abstract: Drawing on and developing Kingdon's multiple streams analysis, this article examines the development of one aspect of the UK's low cost home ownership programme: shared ownership. We demonstrate how key human and non-human policy entrepreneurs were able to set the agenda from 1973–1983 in favour of shared ownership; they neutralized the alternatives, while retaining some of their instruments; and solved a number of early problems by bringing key players into the programme. Our data-sets include a range of archival material and elite interviews. The policy entrepreneurs included John Stanley (who was the housing minister in the First Thatcher government), the National Federation of Housing Associations, and the Building Societies Association. Our development of the multiple streams analysis is to argue that documents, including the lease, act as policy entrepreneurs in their own right. The lease was central to the development of shared ownership and its transformation into a model lease enrolled other organizations, most critically the building societies.